THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE ON THE COMPANY'S MARKET VALUE IN INDONESIA - Atika Kusuma Dewi (LPPM Universitas Trunojoyo Madura, 2023)
This study aims to analyze the effect of Environment, Social Governance (ESG) disclosures on the market value of companies in Indonesia during the COVID-19 pandemic. The sample consists of Indonesian companies listed in the SRI-KEHATI index for 2020-2021. The data was taken from Bloomberg and then analyzed using the regression model. The findings show that ESG disclosure has a significant effect on the company's market value. The results of this study add new evidence to previous findings about the effect of information disclosure, especially related to the environment, social and governance and confirm the signaling theory. The implications of this research are expected to provide investors with material considerations in determining investment. In addition, disclosure of ESG which has a positive influence on market value is expected to contribute to increasing the application of sustainability aspects in the business world in Indonesia. This study has several limitations, namely limited access to websites providing ESG disclosure score data. In addition, the variables used to look at market value factors only use ESG, which based on the results of data processing, there are more than 80% of other factors that can affect market value.